Tata kota menurut Islam : konsep pembangunan kota yang ramah lingkungan, estetik, dan berbasis sosial - Dyayadi, 1966- (Jakarta : KHALIFA, 2008)
Development of city planning from Islamic view point in Indonesia.
Includes bibliographical references (289-291).
Keywords: Cities and towns -- Islamic empire; Urban development